PENGARUH PAJAK DAN RETRIBUSI PARKIR TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA SURABAYA - FAIZATULLAILAH Y C M (Universitas Negeri Surabaya, 2013)
Components of revenue (PAD) is expected to increase revenue (PAD) that Surabaya city in taxes and local retribution. As for the types of local taxes and levies that are interesting to study taxes and parking fees. This study aimed to determine: (1) How much influence does the parking tax revenue (PAD) in Surabaya, (2) How much influence does the parking levy revenue (PAD) in Surabaya, and (3) Is the parking tax and parking levy simultaneously affect the revenue (PAD) in Surabaya. The research used a quantitative approach that is ex post facto that is studying the facts are already there. Describe a process by way of interpreting the data that has been processed. The data used in this study is time series data (time series) during 2005 to 2012 include data: parking tax, parking fees, and revenue of Surabaya. The analysis used is multiple linear regression analysis. Results of multiple linear regression showed that the count of 205 132 F is also supported with a significance level of 0.000 the value is less than 0.05 or 5%, thus H0 is rejected and Ha accepted. This means that the parking tax (X1) and parking fees (X2) has a significant effect simultaneously to local revenues or PAD (Y). Based on the study, the researchers suggested that the withdrawal of taxes and levies penerikannya supervised parking for more leverage and increase the amount of labor because it can help the process of withdrawal and a wide range of areas. Keyword : Tax , Road Pricing , District Own Source Revenue